The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.15380/2277-5706.jcsr.13.046
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pre- and post-donation haematological parameters in plateletpheresis donors

Abstract: Background:Recently the use of single donor platelet (SDP) concentrates has grown steadily due to its employment in chemotherapy protocols. Technical advances in automated cell separators have substantially improved the productivity and quality of the collection of apheresis platelets. Methods: We prospectively studied 90 healthy donors who volunteered for plateletpheresis. We compared the preand post-plateletpheresis haematological values, namely, haemoglobin (Hb), haematocrit, platelet count, mean corpuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Refs. [2,13,16,20,[24][25][26]29] A funnel plot was used to rule out publication bias, which did not observe the statistically significant publication bias. The p value for hemoglobin was 0.57 and 0.47 for hematocrit, and the p value for erythrocyte count was found to be 0.09, which showed that there was no publication bias (Figures 5-7).…”
Section: Resultsmentioning
confidence: 99%
“…Refs. [2,13,16,20,[24][25][26]29] A funnel plot was used to rule out publication bias, which did not observe the statistically significant publication bias. The p value for hemoglobin was 0.57 and 0.47 for hematocrit, and the p value for erythrocyte count was found to be 0.09, which showed that there was no publication bias (Figures 5-7).…”
Section: Resultsmentioning
confidence: 99%